Field-ion specimen preparation using focused ion-beam milling - Larson, D; Foord, D; Petford-Long, A; Liew, H; Blamire, MG; Cerezo, A; Smith, G (1999)
Preparation of field-ion specimens from various materials has been accomplished using focused ion-beam milling in either a simple cutting mode or by application of an annular-shaped ion-milling pattern. These specimens have been investigated using field-ion microscopy and three-dimensional atom probe analysis. In the cutting mode, gallium implantation is minimised when using a lower beam energy. However, with annular milling, using 30 keV ions opposed to 10 keV ions results in less gallium implantation and produces a smaller shank angle and a sharper apex radius. High-dose ion imaging at 30 keV ion energy, even with relatively low beam currents, results in excessive implantation during held-ion specimen fabrication. Focused ion-beam milling provides not only an alternative method of field-ion sample preparation, but also, in conjunction with atom probe analysis, allows the quantitative investigation of the gallium implantation and damage which occurs during the milling. (C) 1999 Elsevier Science B.V. All rights reserved.